Makna Teologi Ekologis dalam Tradisi Roko Molas Poco Ditinjau dari Perspektif Ensiklik Laudato Si’ Artikel 84-88 - Hadut, Aventinus Darmawan; Atu, Laurentius Florido; Camnahas, Antonio (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2023)
Currently, our world is experiencing an ecological crisis, and this can be seen in the polution of water, air and soil. It shows the fractured relationship between human beings and other creatures, in a way that it is not reciprocal, and in which human beings relinquishes his and her responsibilities to the nature and to the other creatures. Responding to this, through Laudato Si’, Pope Francis has called on attention to the ecological emergency. The Pope emphasized on the importance of a reciprocal relationship between the na[1]ture and human to reawaken our human ecological consciousness. However, the author finds that prior to the Church’s ecological appeal, the ecological awareness has already existed within the local Manggaraian culture, namely the roko molas poco. This paper aims at exploring the ecological meanings of the roko molas poco rite and its connection to the Laudato Si. The approach adopted by the authors is the qualitative-descriptive method by reading lit[1]eratures related to the topics discussed. From the study, the authors find that there is similarity in the meaning contained in the rite of roko molas poco and that in the Laudato Si’ appeal. Both have the same goal in improving and building our human ecological awareness. Thus, human ecological awareness can be revived by raising up the values that have already existed in local culture such as roko molas poco